EFFECT OF CORE STABILITY TRAINING ON DYNAMIC BALANCE IN HEALTHY YOUNG ADULTS - A RANDOMIZED CONTROLLED TRIAL (International Journal of Physiotherapy, 2014)
Background: Balance is a key component of normal daily activities. Therefore, it is necessary to find various programs to improve balance. The core functions to maintain postural alignment and balance during functional activities. The purpose was to study the effects of the core stability training on dynamic balance in healthy, young adults.Methods: It was an interventional study, in which 60 healthy young adults were selected. They were randomly divided into two groups of 30 each, one being experimental group and other control group. Measurement of their height, weight, BMI and leg length was taken. Subjects in both the groups were assessed for core stability with pressure biofeedback unit (PBU) and dynamic balance using Star Excursion Balance Test (SEBT) pre and post intervention. Subjects in the experimental group underwent progressive core stability training program for six weeks (3days/week) and control group was refrained from any type of structured training program.Results: There was statistically significant improvement in core stability and dynamic balance of the experimental group after six weeks of intervention.Conclusion: It is concluded that core stability training of six weeks duration is effective in improving dynamic balance in healthy, young adults.